Jewish Victims of Child Sex Abuse: The Holocaust - Chalmers, Beverley (Women in Judaism, 2024)
Jewish children were sexually abused during the Nazi era, although acknowledging this is taboo. Nazi ideology, while advocating killing children, did not promote child sex abuse directly, but did so indirectly by destroying Jewish family life with its normal safeguards for child safety. As a result, children were left vulnerable and unprotected from sexual abuse in homes, villages, ghettos, camps, and hiding places, while those in authority turned a blind eye when Jewish children were sexually assaulted or murdered. Their sexual abuse was then hidden by perpetrators, the children, survivors, rescuers, and Holocaust scholars. Perpetrators were ordinary people who were also Nazis, members of the SS, Einsatzgruppen members, Wehrmacht soldiers, their allies in occupied countries, Russian soldiers at the end of the war, as well as rescuers of children who were hidden in Europe, and those who offered homes to children who were sent to “safety” in countries beyond Europe’s borders. The majority of abusers were Gentiles: a handful were Jewish. For most perpetrators, sexual assault was a crime of opportunity, authority, and violence, often coupled with antisemitic justification, and occasionally, religious vengeance.